Impactos Geoquímicos e Sócio-Ambientais no Estuário do Rio Potengi Região Metropolitana da Grande Natal/RN - Corrêa, Tatiana de Lima (2008)
The present work studied the problems faced riverine populations of the estuary Potengi, detaching its perception with regard to the environment, as well as in the evaluation of the institucional arrangement that acts in the place. Questionnaires were used in five riverine communities and conducted interviews with agents of public agencies and colonies of fishermen. There is little understanding of the needing to preserve and weakness in the application of the regulation mechanisms